Stimulating community participation in a group of farm workers using action research. - P Jagananen (AOSIS, 1999)
This study assessed whether community participation in health related activity was a reality or just popular development rhetoric.Using action research methodology, focus group discussions and informal contacts were made with farm workers consisting of twelve families in Umkomaas, south of Durban in the province of Kwa-Zulu Natal. The aim was to establish whether this community could be actively involved in all aspects of community participation. The level of participation was described using Rifkin's model (Rifkin et al, 1988). Results of this study revealed that the community was able to identify their own health problems, prioritize them and plan appropriate strategies to meet the needs identified.